"Dying With Dignity": A Qualitative Study With Caregivers on the Care of Individuals With Terminal Cancer. (March 2022) - Hayden, Lucy; Dunne, Simon
This study aimed to examine family members' attitudes and perceptions regarding their choice of care in the event of terminal illness, based on their experience in a caregiver's role, while a loved one was terminally ill. All participants ( N = 10) had cared for an immediate family member with terminal cancer. Snowball sampling was used. Qualitative data were collected through in-depth, semi-structured interviews. The data were transcribed verbatim and analyzed using thematic analysis. Five themes were identified from the data. These included two themes relating to participants' experience of care, two themes in relation to participants' attitudes toward the type of care they experienced and a final theme related to the role of religion and spirituality in dealing with loss. The findings of this study support the integration of multidisciplinary healthcare teams and the introduction of holistic care as early as possible within hospitals for individuals with terminal cancer, using the biopsychosocial–spiritual model.